2021
DOI: 10.3390/w13162210
|View full text |Cite
|
Sign up to set email alerts
|

Factors Governing Biodegradability of Dissolved Natural Organic Matter in Lake Water

Abstract: Dissolved Natural Organic Matter (DNOM) is a heterogeneous mixture of partly degraded, oxidised and resynthesised organic compounds of terrestrial or aquatic origin. In the boreal biome, it plays a central role in element cycling and practically all biogeochemical processes governing the physico-chemistry of surface waters. Because it plays a central role in multiple aquatic processes, especially microbial respiration, an improved understanding of the biodegradability of the DNOM in surface water is needed. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 53 publications
1
5
0
Order By: Relevance
“…It explained 6.88 and 28.8% of the total deviance explained in CO 2 and N 2 O models, respectively (Table 2). The positive correlation between the agricultural land cover (Cultivated) and CO 2 concentrations in boreal lakes has been pointed out previously (Kortelainen et al, 2006), likely reflecting inputs of easily degradable DOM (Crapart et al, 2021) as well as nutrient loads from croplands (Rantakari and Kortelainen, 2005). For N 2 O saturation, a positive correlation between N 2 O saturation and agricultural land cover has previously been reported previously for boreal lakes (Kortelainen et al, 2020).…”
Section: The Influence Of Terrestrial Primary Production On Ghg Satur...supporting
confidence: 64%
See 1 more Smart Citation
“…It explained 6.88 and 28.8% of the total deviance explained in CO 2 and N 2 O models, respectively (Table 2). The positive correlation between the agricultural land cover (Cultivated) and CO 2 concentrations in boreal lakes has been pointed out previously (Kortelainen et al, 2006), likely reflecting inputs of easily degradable DOM (Crapart et al, 2021) as well as nutrient loads from croplands (Rantakari and Kortelainen, 2005). For N 2 O saturation, a positive correlation between N 2 O saturation and agricultural land cover has previously been reported previously for boreal lakes (Kortelainen et al, 2020).…”
Section: The Influence Of Terrestrial Primary Production On Ghg Satur...supporting
confidence: 64%
“…This synoptic survey repeated previous campaigns conducted in 1986and 1995(Henriksen et al, 1998. The CBA dataset span a wide range of water quality properties (e.g., DOM, nutrients) (Crapart et al, 2021), catchment properties, and land use (Lie, 2021). Sampling was performed in late fall, during or after lake overturn.…”
Section: Field Surveymentioning
confidence: 99%
“…Recent experimental evidence suggests that such pathways may limit the mineralization rate of humic DOM in nature, explaining its apparent recalcitrance. In laboratory incubations, Crapart et al (2021) showed that DOM from dystrophic Scandinavian lakes can be degraded fairly easily if inorganic N and P are added in excess.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the relative respiration rate of the DOM (Rel. RR, unpublished data), serving as a proxy for biodegradability [48], also exhibited a strong negative correlation with the proportion of VHA (Table 2). This adheres to the fact that the high molecular and aromatic VHA fraction has a lower biodegradability than other DOM moieties.…”
Section: Governing Factors On Dommentioning
confidence: 94%